Estudio jurídico al artículo 185 del código del trabajo ecuatoriano en actual vigencia” “propuesta de reforma - Carrasco Carrasco, Wilson Trajano (2017)
The Social Right, one of the social politics's more important goals constitutes that is inmerso the labor régime inside this, in the regulation of the work in the State, as well as the labor politics's address in general that rests in the productive activity and in the development of the nation in whose régime is affirmed the juridical principles of the personality practically, for that which you/they are dictated social dispositions uninterruptedly in which are important carried out conquests of the labor modern right that make of the labor legislation a true Code of the Work". Walter Linares that qualifies the expression of the Labor Right, "eats a little gleaned, it estimates that he/she can, besides this, to be used indistinctly those of the Right of the Work and that of the Social Right, estimating, however, preferable this last denomination to have, in its opinion "the advantage of including easily inside her all the relative one to the Social security, in this sense such a denomination is more understanding than that of the Right of the Work". Justified the labor régime, I estimate that it is the consequence of a young discipline that to be in full formation, it even presents difficulties for their appointment, being imprecise and generic and even not very technical, the reasons that could show for this consideration characteristic of the nature of the legislation, because being this right the one that spreads to the social justice, seems logical to think that this denomination of Labor Right reaches him/her, because guard narrows relationship with the call social question, to the one that is bound doctrinal and historically; because still when all right has in certain sense, a social meaning, this has it in a more special way, as reaction against individualistic systems, for they contain a wider content that the other denominations, not in the sense that he/she is justified more its employment for the fact of understanding bigger number of matters, but because, given the wide field of these, and of people to those that it reaches. The Labor Right, well-known as régime of the Work, it arises in Ecuador, with the pronouncement of the result of the convergence of national factors and international, among the first it can stand out the industrial development that generates and it organizes to the labor class under conditions of claiming their rights, among the international aspects, we should enumerate, the Russian Revolution that encourages and it invigorates the world socialism, the creation of the Commission of International Legislation of the Work, and the operation of the International Office of the Work, the work of the International Conference of the Work, among other, and that whose object was centered in the establishment of the peace, and this won't be able to be carried out but on the bases of the social justice. The labor right, as group of principles, precepts and rules to those that are subjected the relationships coming from the work, it is in Ecuador an artificial new discipline that has intended to structure the components to sustain it legally, as it was it with the first labor laws, as the social Julian legislation, until the promulgation of the Code of the Work, in the year of 1938. According to the ends of the right of the work, some authors manifest us, from their points of view, as Trueba Urbina, manifestos that you/they tell us that: "right of the work is a group of principles, norms and institutions that protect, they dignify and they spread to claim to all those that live off its material or intellectual efforts, for the realization of its historical destination, as it is it to socialize the human" life.